Video Path Selection for Traffic Engineering in SDN - Adiluck Chooprateep (2020)
© 2019 IEEE. This paper proposes the video path selection algorithm for traffic engineering in SDN called Video Path Selection Algorithm (VPSA). The proposed algorithm uses the past and the latest bandwidth usage data collected by the controller for calculating a suitable path. If there is no suitable path for the video request, this algorithm can choose the mode whether it will reject or accept the requests with reduced bandwidth rate. The performance of the proposed algorithm is compared with Bandwidth Guaranteed routing algorithm using Holding Times (BGHT) and Shortest-Distance Path algorithm (SDP). The evaluation results show that the proposed algorithm has the accepted number of video requests more than the other algorithms in the rejected traffic mode. Moreover, the proposed algorithm also has the amount of reduced bandwidth lower than the other algorithms in the non-rejected traffic mode.